Functional and Sensory Properties of Fermented Locust Bean Seeds Using Optimized Pre-Fermentation Conditions - Koledoye, A.O.; Akanbi, C.T. (Ife Journal of Technology, 2015)
This study is a continuation of previous work set to establish optimal processing conditions for the production of fermented locust bean seeds. The effect of employing these already determined conditions (First cooking at 50 kPa for 54 min per 100 g of seed and second cooking time of 15 min per 90 g of seed) on anti-nutritional factors, functional and sensory properties of the product was determined. The functional properties investigated were water and oil absorption capacity, emulsion capacity and solubility while tannin, phytate and oxalate were the anti-nutritional factors determined. Water absorption capacity and emulsion capacity decreased with dehulling but were increased by fermentation and drying while the oil absorption capacity and solubility decreased with processing. There was significant reduction in all anti-nutritional factors investigated. The consumer preference for taste and mouth-feel of both the traditionally and optimally processed Iru were significantly comparable (p<0.05). There was a significant difference in the preference for colour, aroma, texture, and overall acceptability. The study concluded that processing locust bean seeds under optimized conditions yields a product with acceptable nutritional benefits.